Pedagogical teacher training of the Scientific, Technological and Professional Education in Brazil: brief history and contemporary challenges (Práxis Educativa, 2024)
In this article, the pedagogical training of teachers in Professional, Scientific and Technological Education is approached from a brief history, its legal aspects, the first manifestations, the perspectives and its contemporary challenges, in an attempt to highlight discussions about teacher training in the context of Professional and Technological Education. It was found, through this bibliographical review, that, since the initial preparation, this training appears to be distant from theoretical concepts that relate the World of Work and Education. This is a qualitative investigation, with a bibliographical survey of literature that discusses historical, political aspects and the challenges of training for Professional, Scientific and Technological Education in Brazil. The results point to the need to reformulate policies aimed at teacher training, especially given the expansion of the offer of Professional and Technological Education, the singularities of the modality and the demands it imposes on teachers.Keywords: Pedagogical training of teachers. Continuing training. Professional and Technological Education.